Analysis of the Effectiveness of Budget Management of Additional Employee Income (TPP) at the Youth and Sports Office of Papua Province - Risally Imelda Retraubun; J. Ary Mollet; Risky Novan Ngutra (LPPM STIE Krakatau, 2025)
Purpose: This study examines the effectiveness of Employee Performance Supplement (TPP) budget management at the Papua Province Youth and Sports Office, focusing on output, outcome, and key implementation challenges. Research/methodology: This study uses a qualitative approach with data collection techniques through interviews, documentation, and budget and staffing document reviews. Results: The TPP’s administrative management is effective, shown by proper documentation and budget realization. However, its role as a performance incentive remains weak since TPP amounts are not yet linked to attendance or measurable results, limiting its impact on discipline and productivity. Conclusions: TPP budget management is administratively effective but weak in boosting performance. Incentives are not tied to attendance or output, and delays plus poor evaluation reduce its motivational impact. Limitations: This study is limited to a single institution, with a small sample size and no quantitative performance metrics, which restricts the generalizability and depth of the analysis. Contribution: This study highlights the gap between budget compliance and performance outcomes, and offers recommendations for integrating attendance and performance data into the incentive system.